Adaptive robust control with extended disturbance observer for motion control of DC motors. Issue 22 (8th October 2015) - Yang, Yanyu; Wang, Yong; Jia, Ping
Abstract : This Letter proposes an extended disturbance observer (EDO) based adaptive robust control method for motion control of DC motors. An adaptive part for structured uncertainties, an EDO for unstructured uncertainties and a feedback robust law for global robustness are designed in this method. The theoretical analysis guarantees a prescribed tracking performance under various uncertainties and comparative numerical simulation shows the excellent high‐precision performance of proposed method on DC motor motion control.